From the profession of photographer to the transcendent work: Martín Chambi in Cusco - Garay Albújar, Andrés (2011)
Martín Chambi's photographic work has always provoked voices of all kinds, both in his professional life and in recent times. He is the Peruvian photographer about whom the most has been said and written both in the country and abroad, but the paradox is that there is no consensus for a basic understanding of his work. And maybe that will never happen. There are those who consider their work as a simple trade, nothing transcendent; while others reinvent it at the level of surrealist work. Only in an approximation to the history of a photographer, to the context where he worked, to his intentions in the use of his images, and to his photographic practices, and considering what he himself said, can one properly understand the value of his images. . Because the photographic image is polysemic and protean, and taking into account the complexity of Chambi's collection, due to its form and content, it is important to insist on an approach to the type of photographs that he developed in order to understand him as an author of images, beyond the artistic and commercial functionality that the work may have had at the time. This essay attempts to locate in the history of photography in Cusco and the southern Andean region those photographic practices and uses developed by Martin Chambi: in terms of professional photography, we will see artistic portraits in studio, the commissions that were requested of him, the activity he had with print media, his documentary photography, and photographic exhibitions.